GE_GERICHTE A/1560/2003 vom 15. Juni 2006 - GE Cour de justice (2006)
AI(ASSURANCE) ; FIBROMYALGIE ; DÉPRESSION ; AFFECTION PSYCHIQUE ; COMORBIDITÉ ; CARACTÈRE DE MALADIE ; FORCE PROBANTE ; EXPERTISE MÉDICALE | LAI4